Integrating Five Theories in Pursuit of Marketing Success in Gamification Interventions: A Conceptual Paper - Mgiba, Freddy Marilahimbilu (International Review of Management and Marketing, 2019)
The study was motivated by the novelty of Gamification and the possible impact of its growth in the marketing space. It synthesizes information gleaned from gamification literature, to isolate common themes in order to produce a set of researchable propositions that can in turn be quantitatively tested, and to link those common themes to well-known academic grounding theories in order to advance further understanding of the concept. The study was based on the review of available literature on gamification and on the five theories that are deemed relevant for better understating of the gamification industry, and concludes by giving a list of propositions and suggesting a research framework which shows the linkages between access to gamification technology, customization of technology, congruence between expectations of gamification instigators and users, communication between companies with gamified interventions and customers, the attractiveness of the gamification technology, and the feelings of reciprocity as perceived by customers. The proposed framework, in turn, shows how these variables are related to getting people motivated to adopt gamification as a marketing tool. As the study was based on available literature, it shares the limitations contained therein. Keywords: Gamification, grounding theories, customization, motivation, congruence, reciprocity, attractiveness JEL Classifications: L86; M3; M16 DOI: https://doi.org/10.32479/irmm.7174